Obtaining of fermented beverages with carrot pomace - Косоголова, Л. О.; Турбовська, С. В. (Problems of Environmental Biotechnology, 2020)
The parameters of extraction of extractives from carrot extracts are investigated in the article. The optimal ratio of the components of the enzymatic beverage was selected, namely (60:40) water extract of carrot buds and concentrate of kvass wort. The optimal parameters of fermentation of wort with carrot extract were determined. Fermentation time - 4 days. Rational parameters of pasteurization and shelf life of fermented beverage have been established. The physicochemical and organoleptic parameters of the finished fermented beverage "Student" have been determined.